(untitled) (Environment & Health, 2019)
Objective: We defined the problem issues of the monitoring of health preserving competence among modern adolescents in the light of the changes in their lifestyle affecting health. Material and methods: We used the data of the surveys of the groups of the students aged 14-17 at the secondary schools of the city of Vinnytsia in 2003, 2009, 2013, 2017. Statistical processing was performed by Statistica 6.1 software, including such methods as descriptive statistics, the Student’st-test for independent groups, the Cochran Qtest, the Spearman rank R. Results: The results of the fifteen years of research show that the life style of the adolescents is changing, but there is no unanimous answer to the question whether it is becoming more or less beneficial for their health. On the average, half of the adolescents have the insufficient knowledge on some practical issues in the field of health preservation, such as methods for prevention of acute respiratory viral infections, pre-medical actions in case of burns, food poisoning, methods of the calculation of calories intake, etc. In particular, knowledge of the adolescents in the field of contraception was improved, there was no positive shift in their understanding of the risks of the early beginning of sexual life, however. The popularity of various “gadgets” have affected the forms of pastime: instead of watching TV adolescents spend much time at PC; they stay outdoors more, but it does not mean that they have an active lifestyle. Mobile phones and Internet have become one of the causes of significant sleep deficiency. At the same time, the results of our research have shown an increase in physical activity, a decrease in the first and subsequent attempts of smoking among young men, a decrease in the number of girls with the formed habit of smoking. There is a shift in the first attempts of drinking alcohol to later adolescent age, the number of young men who had ever been drunk has also decreased. Conclusions: Comparison of the separate indicators of health literacy, determination of the motivation to the health lifestyle and behavioural risks among adolescents have demonstrated that monitoring of health-preserving competence should be conducted simultaneously in the three directions mentioned above, taking into account the current tendencies and gender peculiarities of the formation of health-preserving behaviour among adolescents, as well as the impact of social changes and scientific and technical progress on such a behaviour. At the development of this monitoring the following features should be taken into account: complexity, conciseness, sensitivity, gender, age, openness to new modifications.